Inductive Picture Word Models and Picture Word Cards in Basic Literacy for Students: Model Picture Word Inductive dan Kartu Kata Bergambar pada Literasi Dasar Siswa - Lovita, Nuria; Aisyah, Siti; Ismira (Universitas Muhammadiyah Sidoarjo, 2025)
General background: Literacy is a fundamental competency in primary education, with early reading and writing forming the foundation for lifelong learning. Specific background: However, many second-grade students at SD Negeri 10 Pasar Melintang Tapan still struggle to meet minimum literacy standards, partly due to monotonous teaching methods and limited instructional media. Knowledge gap: While the Picture Word Inductive (PWI) model has been recognized for its potential, its integration with picture word cards in the context of Indonesian primary schools has been underexplored. Aims: This study examined the effectiveness of the PWI model supported by picture word cards in improving students’ beginning reading and writing skills. Results: Using a quasi-experimental non-equivalent control group design with 42 students, findings revealed significant improvements in the experimental group compared to the control group. Posttest reading scores (79.77 vs. 74.25) and writing scores (82.45 vs. 76.75) demonstrated higher achievement with strong statistical support (p < .001). Novelty: The study contributes evidence that combining inductive vocabulary strategies with visual media enhances literacy acquisition more effectively than conventional methods. Implications: These results suggest that integrating PWI and picture word cards can serve as a practical and scalable strategy to strengthen national literacy initiatives in early grades. Highlight: • Model PWI with word cards improved early reading and writing• Experimental group scored higher than conventional method group• Supports strengthening of basic literacy in primary school students Keywords: Picture Word Inductive Model, Word Cards, Reading Skills, Writing Skills, Literacy